2018
DOI: 10.1002/ejoc.201800980
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic Access to Chiral Tetrols Produced by Thiamine Diphosphate Dependent Benzaldehyde Lyase

Abstract: Highly functionalized polyol building blocks have been synthesized by means of stereoselective chemoenzymatic C–C bond formation followed by stereoselective reduction. Catalysis by thiamine diphosphate (ThDP) dependent benzaldehyde lyase (BAL) with glyceraldehyde acetonide as acceptor substrate gave highly stereoenriched polyols such as (1S,2S,3R)‐1‐phenylbutane‐1,2,3,4‐tetrol (1), the 3,4‐protected anti‐1,2‐diol 5, and the precursor of both compounds, 2‐hydroxyketone 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Previously, we have shown that BAL ligates benzaldehyde and acetonide‐protected glyceraldehyde . The latter can be obtained by performing a formyl elongation of the 2‐hydroxy aldehyde glycolaldehyde with KdcA and thus could be used for the biocatalytic formation of enantiopure building blocks such as (1 S ,2 S ,3 R )‐1‐phenylbutane‐1,2,3,4‐tetrol . Aldolases are also known to convert hydroxy aldehydes for the synthesis of highly functionalised polyols and might be used in bienzymatic cascades with KdcA…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we have shown that BAL ligates benzaldehyde and acetonide‐protected glyceraldehyde . The latter can be obtained by performing a formyl elongation of the 2‐hydroxy aldehyde glycolaldehyde with KdcA and thus could be used for the biocatalytic formation of enantiopure building blocks such as (1 S ,2 S ,3 R )‐1‐phenylbutane‐1,2,3,4‐tetrol . Aldolases are also known to convert hydroxy aldehydes for the synthesis of highly functionalised polyols and might be used in bienzymatic cascades with KdcA…”
Section: Methodsmentioning
confidence: 99%
“…Acetonide-protected glyceraldehyde, the product of FSA and KdcA, is a valuable building block for the synthesis of stereoenriched polyols such as (1S,2S,3R)-1-phenylbutane-1,2,3,4-tetrol. 200 In 2017, a cascade with ThDP-dependent FLS and aldolase FSA to generate chiral carbohydrates was outlined, which illustrates the great potential of this kind of enzyme combination. 201 The high reactivity of formaldehyde can also result in nonenzymatic reactions in the biochemical environment.…”
Section: Review Synthesismentioning
confidence: 99%
“…Moreover, 1,4-diketones have been shown to be useful building blocks for the preparation of cyclopentenones and five-membered heterocycles, which are found in numerous natural products . Several methods for the synthesis of γ-diketones have been described, but many are neither generalizable nor convenient, are not ecofriendly, and show poor stereoselectivity. Thus, a practical and stereoselective reaction that operates under mild conditions is obviously highly desirable.…”
mentioning
confidence: 99%